Pengujian Prospect Theory: Dampak Hasil Pertandingan Sepakbola SEA Games terhadap Return Saham di Indonesia Tahun 1997-2011 - , Epsi Euriga ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Motivated from the many psychological facts which show that the results of sporting events have a strong impact on mood, this study investigates the impact of the results of the SEA Games football match in the stock market in Indonesia in 1997-2011. The results show a negative abnormal returns are larger after a soccer losses than a positive abnormal return after SEA Games soccer match winning. The impact of the soccer losses aginst the value index that proxied by the price-to-book ratio and the index stocks with small market capitalization proved statistically significant. Despite the soccer loss impact between the value index and the growth index have no significant difference. In addition, the results of football matches have no effect on the volume of trade